The Peacekeepers - Cowan, Paul (St-Arnauld, Johanne, 2004)
Duration: 01:30:00 This Canadian documentary film provides a highly complex and detailed investigation into the activities of the UN peacekeeping forces in the African Congo. The troopes were stationed in Congo throughout the year 2004, while the world's attention was focused on the events in Iraq. At the time, the situation in the country was threatening to turn into a tragedy far too reminiscent of that which befeel Rwanda in 1994. Competing tribes, often connected to the mafia and conscripting large numbers of child soldiers, were fighting for controly over the diamond and gold mines in the Eastern part of the country. Innocent civilians suffered the most, the death toll numbering hundreds just during the year and a half that the film was shot. The film also presents footage of the complicated negotiations at the UN headquarters in New York regarding the Congo situation and limited scope of help that the "peacekeepers" could provide to those most in need of it. Between 1994 and 2004 almost fourty members of the peacekeeping force lost lives. The total financial assistance reached a billion dollars per year. Even if the UN partially succeeded in stabilizing the situation in the country, the real imput of the interference is yet to be evaluated.